2021
DOI: 10.1039/d1gc01979a
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the active sites and demonstrating stable catalyst for the cost-effective conversion of ethanol to 1-butanol

Abstract: The recent emergence of a robust renewable ethanol industry has provided a sustainable platform molecule toward the production of value-added chemicals and fuels; what is lacking now are viable conversion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Figure 4 depicts three biorefinery models for fuel and chemical production through butanol production from ethanol. For flowsheet A‐nBuOH and flowsheet C‐nBuOH, either all or a fraction of the ethanol is converted to butanol co‐product via a Guerbet process 10–13 . After butanol recovery, the remaining ethanol is converted to olefins that are oligomerized using a two‐step process 13 and then hydrogenated to hydrocarbon fuels.…”
Section: Methodology and Process Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 depicts three biorefinery models for fuel and chemical production through butanol production from ethanol. For flowsheet A‐nBuOH and flowsheet C‐nBuOH, either all or a fraction of the ethanol is converted to butanol co‐product via a Guerbet process 10–13 . After butanol recovery, the remaining ethanol is converted to olefins that are oligomerized using a two‐step process 13 and then hydrogenated to hydrocarbon fuels.…”
Section: Methodology and Process Descriptionmentioning
confidence: 99%
“…For flowsheet A-nBuOH and flowsheet C-nBuOH, either all or a fraction of the ethanol is converted to butanol co-product via a Guerbet process. [10][11][12][13] After butanol recovery, the remaining ethanol is converted to olefins that are oligomerized using a two-step process 13 and then hydrogenated to hydrocarbon fuels. For flowsheet B-nBuOH, all the ethanol is converted to butanol co-product while hydrocarbon fuel is produced from the bioconversion residuals using an HTL process.…”
Section: Conversion Routes Of Ethanol To Produce Hydrocarbon Fuels An...mentioning
confidence: 99%
“…Acetaldehyde was observed to be selective on Cu/ t -ZrO 2 , whereas Cu/ m -ZrO 2 showed a high selectivity for ethyl acetate, which was described by the mobility of oxygen from zirconia to a copper site resulting in electron transfer between support and copper . Guo et al utilized single atom Cu 1+ sites on MgAl mixed oxide support to demonstrate a highly selective conversion of ethanol to higher alcohols such as butanol . At low loading of copper on MgAl oxide support, a high dispersion of single atom Cu 1+ sites is achievable, which showed high stability up to 150 h TOS run while maintaining the selectivity for butanol .…”
Section: Catalysts For Ethanol Dehydrogenation and Decompositionmentioning
confidence: 99%
“…Guo et al utilized single atom Cu 1+ sites on MgAl mixed oxide support to demonstrate a highly selective conversion of ethanol to higher alcohols such as butanol . At low loading of copper on MgAl oxide support, a high dispersion of single atom Cu 1+ sites is achievable, which showed high stability up to 150 h TOS run while maintaining the selectivity for butanol . Pinzón et al developed a calcium based bifunctional acid–base catalyst for ethanol condensation to n -butanol and conducted in situ DRIFT-MS studies to understand the mechanism on the acid–base sites .…”
Section: Catalysts For Ethanol Dehydrogenation and Decompositionmentioning
confidence: 99%
“…However, the weak dehydrogenation/hydrogenation over Lewis acid/base sites restrains the ethanol valorization . Considering both perspectives, tailoring the acid–base catalysts by introducing transition metal species (such as Co, Ni, Cu, , Zn, and Pd) as dehydrogenation sites might improve the performance toward higher alcohols. Cu has been frequently chosen as a dehydrogenation catalyst for ethanol conversion. , Recently, Ramasamy and co-workers reported that Cu/Mg x Al y O achieved 75% 1-butanol and higher alcohol selectivity at 59% ethanol conversion .…”
Section: Introductionmentioning
confidence: 99%